Cytoprotective effect of benzyl n'-(5-chloro-indol-3-ylmethylidene)- hydrazinecarbodithioate against ethanol-induced gastric mucosal injury in rats - Hashim, H.; Ali, Hapipah Mohd; Khaledi, H.; Ameen, M.; Mughrabi, F.F. (2012)
Indolic compounds have attracted a lot of attention due to their interesting biological properties. The present study was performed to evaluate the subacute toxicity and anti-ulcer activity of BClHC against ethanol-induced gastric ulcers. Experimental animal groups were orally pre-treated with different doses of BClHC (50, 100, 200 and 400 mg/kg) in 10% Tween 20 solution (vehicle). Blank and ulcer control groups were pre-treated with vehicle. The positive group was orally pretreated with 20 mg/kg omeprazole. After one hour, all groups received absolute ethanol (5 mL/kg) to generate gastric mucosal injury except the blank control group which was administered the vehicle solution. After an additional hour, all rats were sacrificed, and the ulcer areas of the gastric walls determined. Grossly, the ulcer control group exhibited severe mucosal injury, whereas pre-treatment with either derivative or omeprazole resulted in significant protection of gastric mucosal injury. Flattening of gastric mucosal folds was also observed in rats pretreated with BClHC. Histological studies of the gastric wall of ulcer control group revealed severe damage of gastric mucosa, along with edema and leucocytes infiltration of the submucosal layer compared to rats pre-treated with either BClHC or omeprazole where there were marked gastric protection along with reduction or absence of edema and leucocytes infiltration of the submucosal layer. Subacute toxicity study with a higher dose of derivative (5 g/kg) did not manifest any toxicological signs in rats. In conclusions, the present finding suggests that benzyl N'-(5-chloroindol-3- ylmethylidene)hydrazinecarbodithioate promotes ulcer protection as ascertained by the comparative decreases in ulcer areas, reduction of edema and leucocytes infiltration of the submucosal layer.